2017
DOI: 10.2485/jhtb.26.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Masticatory Muscles Function in Different Malocclusion Cases Using Surface Electromyography

Abstract: A malocclusion is a misalignment or incorrect relation between the teeth of the two dental arches when they approach each other as the jaws close. It has been suggested that masticatory function varies in relation to different malocclusion. Thereby, masticatory muscle can be affected with different malocclusion as masticatory process is related with this. The aim of this study was to evaluate the function of masticatory muscles (masseter and temporalis muscles) in patient with different malocclusion by surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…The imbalance of sex distribution can affect the masticatory strength during mastication on both the crossbite and noncrossbite sides. 3 There were significant differences in superficial masseter muscle activity in all types of malocclusions on the crossbite and non-crossbite sides, meanwhile the activity of the superficial masseter muscle was not significantly different between groups in class I malocclusion on the crossbite side and class II malocclusion on the non-crossbite side. These results indicated that the non-crossbite side class II malocclusion had the same muscle activity as the crossbite side class I malocclusion but with lower than normal activity on the non-crossbite side of the class I malocclusion.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The imbalance of sex distribution can affect the masticatory strength during mastication on both the crossbite and noncrossbite sides. 3 There were significant differences in superficial masseter muscle activity in all types of malocclusions on the crossbite and non-crossbite sides, meanwhile the activity of the superficial masseter muscle was not significantly different between groups in class I malocclusion on the crossbite side and class II malocclusion on the non-crossbite side. These results indicated that the non-crossbite side class II malocclusion had the same muscle activity as the crossbite side class I malocclusion but with lower than normal activity on the non-crossbite side of the class I malocclusion.…”
Section: Discussionmentioning
confidence: 75%
“…Angle class III malocclusions are denoted by the mesiobuccal groove of the permanent mandibular first molar being more medially located than the mesiobuccal cusp of the permanent maxillary first molar. 3 The presence of one or more posterior group teeth in an irregular bucco-lingual or bucco-palatal relationship with one or more opposing teeth in centric occlusion is defined as posterior crossbite. Posterior crossbite, especially unilateral posterior crossbite, can cause mandibular shift, postural changes and has a possible link to temporomandibular joint (TMJ) disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For the masseter muscle, the electrodes were placed antero-superiorly to the angle of the mandible over the muscle. While for the temporalis muscle, a line was drown from the upper ear-line to the canthus of the eye and the electrodes were placed above this line, Nishi et al 9 The two recording electrodes were placed on the determined muscle location and the reference electrode was placed on the sternocleidomastoid muscle in the neck (Figure2) . The electrodes placed on the skin, connected to the sEMG device via the electrode cable and the sEMG device was connected to the PC.…”
Section: Methodsmentioning
confidence: 99%
“…TMD on its different types and levels of severity may affect an important function of the stomatognathic system, namely chewing. The process of chewing involves mandibular movements associated with the masseter, temporalis, medial, and lateral pterygoid muscles . In healthy subjects, the chewing should occur bilaterally, with both sides alternating the bolus .…”
Section: Introductionmentioning
confidence: 99%